Preparation method of N-substituted pyrrole compound
By catalyzing the reaction of 2,5-hexanedione and amine compounds using metal organic framework materials, the problems of low selectivity of N-substituted pyrrole compounds and expensive catalysts in the prior art are solved, and an efficient and low-cost preparation method is achieved.
Patent Information
- Application Number
- CN202311146067.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
In the prior art, the selectivity of N-substituted pyrrole compounds or the catalyst requires expensive metals, resulting in high production costs and low efficiency.
Using metal organic framework materials as catalysts, the efficient preparation of N-substituted pyrrole compounds is achieved by contacting 2,5-hexanedione and/or furan compounds with amine compounds in the presence of liquid phase diluents and catalysts.
It improves reaction efficiency and product yield, reduces production costs, and provides a new idea for green synthesis of pyrrole compounds.
Smart Images

Figure CN119569634A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an N-substituted pyrrole compound. Background Art
[0002] In order to achieve sustainable economic development, the development of renewable lignocellulosic biomass to replace fossil energy for the production of carbon-containing chemicals and fuels has attracted increasing attention. They are the only widely available carbon source besides petroleum and coal, and can be easily converted into several important platform compounds with many useful chemical bonds, such as nitrogen heterocycles.
[0003] Nitrogen-containing heterocycles, especially functionalized pyrroles, are important structural units of a large number of naturally occurring and pharmacologically active molecules. They are widely used in the core structures of bioactive substances such as vitamins, anticancer drugs, and antibacterial drugs. The main substrates used in traditional N-substituted pyrroles are usually ketones, aldehydes, or amines containing substituents. Most of these raw materials come from petrochemical resources, and the reaction yield is low. 2,5-Hexanedione (HDO) or 2,5-dimethylfuran (DMF) has attracted more and more attention as an important biomass platform compound. Researchers synthesize HDO or DMF through cellulose or sugar platforms. HDO or DMF can react with amines or nitro compounds under the catalysis of appropriate catalysts to undergo Paal-Knorr condensation to generate N-substituted pyrroles. Under suitable catalysts and reaction conditions, high selectivity and yield can be obtained. Patent document CN103288701A discloses a 1,5-diaryl pyrrole derivative, which is prepared by reacting a 1,4-dicarbonyl compound with an amine compound under the catalytic action of a protonic acid. The yield of most embodiments is about 40-60%.
[0004] Prior art [New J.Chem.2017,21,12339-13184] proposed an efficient deep eutectic solvent-based [CholineCl][ZnCl 2 ] 3 A method for synthesizing pyrrole, which can achieve a higher yield, but is not suitable for large-scale production due to its high energy consumption and the use of a eutectic solvent. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low selectivity of N-substituted pyrrole compound products or the need for expensive metals in the catalyst in the prior art, and to provide a method for preparing N-substituted pyrrole compounds; the preparation of N-substituted pyrrole compounds by catalysis of metal organic framework materials has outstanding characteristics such as high reaction efficiency and high product yield.
[0006] In order to achieve the above object, the present invention provides a method for preparing an N-substituted pyrrole compound, the method comprising:
[0007] In the presence of a liquid diluent and a catalyst, 2,5-hexanedione and / or a furan compound is contacted with an amine compound;
[0008] The catalyst contains a metal organic framework material, and the metal organic framework material includes:
[0009] Metal center; and
[0010] an organic ligand coordinated to the binding site of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities;
[0011] The metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al; the organic ligand is selected from at least one of carboxylic acid organic ligands and / or polyazole organic ligands.
[0012] Through the above technical scheme, the present invention uses metal organic framework materials to catalyze the preparation of N-substituted pyrrole compounds (such as 2,5-dimethyl N-substituted pyrrole compounds) for the first time, which can achieve high reaction efficiency and high product yield. The development of this method will provide new ideas for the construction of green synthetic pyrrole compounds, provide a new direction for metal organic framework materials in the field of biomass catalysis, and achieve unexpected technical effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The scanning electron microscope (SEM) images of Cu-BTC and Cu-BTC-BzIm in Example 1;
[0014] Figure 2 It is the pyridine desorption infrared (Py-FTIR) image of Cu-BTC and Cu-BTC-BzIm in Example 1;
[0015] Figure 3 is the contact angle between Cu-BTC and water in Example 1;
[0016] Figure 4 is the contact angle between Cu-BTC-BzIm and water in Example 1;
[0017] Figure 5 N is the N of Cu-BTC and Cu-BTC-BzIm in Example 1 2 - Adsorption-desorption curve;
[0018] Figure 6 is a scanning electron microscope (SEM) image of Cu-BTC-BzIm-2 in Example 2;
[0019] Figure 7The pyridine desorption infrared images of Cu-BTC and Fe-Cu-BTC prepared in Example 11;
[0020] Figure 8 2. XRD diagram of Cu-BTC and Fe-Cu-BTC obtained in Example 11. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] In the present invention, MOFs materials refer to metal organic framework materials or metal organic skeleton materials.
[0023] In the present invention, the metal center refers to the metal ion used to form a coordination complex in the MOFs material.
[0024] The present invention provides a method for preparing an N-substituted pyrrole compound, the method comprising:
[0025] In the presence of a liquid diluent and a catalyst, 2,5-hexanedione and / or a furan compound is contacted with an amine compound;
[0026] The catalyst contains a metal organic framework material, and the metal organic framework material includes:
[0027] Metal center; and
[0028] an organic ligand coordinated to the binding site of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities;
[0029] The metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al; the organic ligand is selected from at least one of carboxylic acid organic ligands and / or polyazole organic ligands.
[0030] The use of metal organic framework materials to catalyze the preparation of N-substituted pyrrole compounds can achieve high reaction efficiency and high product yield.
[0031] According to a preferred embodiment of the present invention, the metal of the metal center is selected from at least one of Zn, Cu, Ni, Fe, Co, Ag and Zr.
[0032] According to a preferred embodiment of the present invention, the carboxylic acid organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid and 3,3,5,5-biphenyl tetracarboxylic acid.
[0033] According to a preferred embodiment of the present invention, the polyazole organic ligand is selected from at least one of benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxybenzene)benzimidazole, 2-aminobenzimidazole and 2-(4'-thiazole)benzimidazole.
[0034] According to a preferred embodiment of the present invention, the metal organic framework material is a dual ligand MOFs material, comprising:
[0035] Metal center; and
[0036] The carboxylic acid organic ligand and the polyazole organic ligand coordinated with at least two binding sites of the metal center form an at least partially crystalline network structure with multiple internal pores. The use of the dual-ligand MOFs material is conducive to improving conversion rate and selectivity.
[0037] According to a preferred embodiment of the present invention, the contact angle between the dual-ligand MOFs material and water is 40-120°, preferably 40-100°.
[0038] According to a preferred embodiment of the present invention, the dual-ligand MOFs material crystal has a wrinkled outer surface; preferably, clustered flake-like protrusions are distributed on the surface of the dual-ligand MOFs material crystal to form a wrinkled outer surface.
[0039] According to a preferred embodiment of the present invention, the total acid content of the dual-ligand MOFs material is 30-500 μmol·g -1 , preferably 40-400 μmol·g -1 .
[0040] According to a preferred embodiment of the present invention, the total specific surface area of the dual-ligand MOFs material is 900-1800 m 2 ·g -1 , external specific surface area is 40-200m 2 ·g -1 .
[0041] According to a preferred embodiment of the present invention, the total pore volume of the dual-ligand MOFs material is 0.4-1.0 cm 3 ·g -1 , the micropore volume is 0.2-0.9cm 3 ·g -1 .
[0042] In the present invention, the total pore volume of the dual-ligand MOFs material is the sum of the micropore volume and the mesopore volume.
[0043] The dual-ligand MOFs materials having the aforementioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the dual-ligand MOFs material of the present invention, which comprises the following steps:
[0044] S1, dissolving a soluble metal salt and a carboxylic acid organic ligand in a solvent I, crystallizing, separating, and first drying to obtain a MOFs material formed by the metal and the organic ligand I;
[0045] S2, contacting the MOFs material in step S1 with a solution containing polyazole organic ligands and alkaline substances; separating, washing, and performing a second drying to obtain the dual-ligand MOFs material.
[0046] The coordinated water molecules of the dual-ligand MOFs material of the present invention are easily removed during the preparation process, forming an open metal center as a catalytic center; through the ligand exchange method, the polyazole ligand containing a benzene ring has a strong alkalinity, so that the pore surface properties of the dual-ligand MOFs material are easier to control, and the nitrogen atom donor participates in the coordination, so that it has a certain hydrophobicity compared to before the ligand exchange; the newly formed metal open site increases the acid content of the material, and the newly formed mesoporous cavity effectively promotes the diffusion of the substrate, which is not only beneficial to the substrate adsorption and product desorption, and increases the yield of the target product, but also inhibits the deactivation of the catalyst.
[0047] In the present invention, there is no particular limitation on the type of the soluble metal salt, and it may be, for example, a soluble salt such as a metal nitrate, a metal chloride, or a metal sulfate.
[0048] In the present invention, in step S1, the optional range of the dosage ratio of the soluble metal salt to the organic ligand I is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of the soluble metal salt to the organic ligand I is 1:0.2-5.
[0049] In the present invention, in step S1, the optional range of the usage ratio of solvent I to soluble metal salt is relatively wide. According to a preferred embodiment of the present invention, the usage ratio of solvent I to soluble metal salt is 5-100 mL solvent I / 1.0 g soluble metal salt.
[0050] In the present invention, in step S2, the optional range of the usage ratio of MOFs material to organic ligand II is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of MOFs material to organic ligand II is 1:(0.01-5).
[0051] In the present invention, in step S2, the optional range of the usage ratio of MOFs material to alkaline substance is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of MOFs material to alkaline substance is 1:(0.01-3).
[0052] In the present invention, in step S2, in the solution containing organic ligand II and alkaline substance, the range of solvents available for selection is relatively wide. According to a preferred embodiment of the present invention, the solvent is solvent II, and solvent II is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene and ethylbenzene. Preferably, the mass ratio of MOFs material to solvent II is 1:(2-200).
[0053] In the present invention, in step S2, the type of the alkaline substance can be selected from a wide range, as long as it is an organic base or an inorganic base with weak alkalinity. According to a preferred embodiment of the present invention, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, ammonia water and aniline.
[0054] According to a preferred embodiment of the present invention, the method for preparing the metal organic framework material further includes, in step S2, immersing the washed solid in a solvent III, wherein the solvent III is selected from at least one of methanol, ethanol, dichloromethane and acetone; the preferred immersion conditions include: the immersion temperature is 0-50°C; the mass ratio of the solid to the solvent III is 1:10-300.
[0055] In the present invention, the soaking time can be determined according to actual needs. According to a preferred embodiment of the present invention, the soaking time is 10-96 hours, and the solvent III is replaced every 2-24 hours.
[0056] In the present invention, in step S1, the range of crystallization conditions is relatively wide. According to a preferred embodiment of the present invention, the crystallization conditions include: a crystallization temperature of 30-200°C, preferably 50-160°C; the reaction time can be reasonably determined according to actual needs, preferably, the crystallization time is 3-44h, preferably 5-24h.
[0057] In the present invention, in step S1, the first drying condition has a wide range of optional options. According to a preferred embodiment of the present invention, the first drying condition includes: a drying temperature of 70-200°C; the drying time can be reasonably determined according to actual needs, and the drying time is 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.
[0058] In the present invention, in step S2, the contact conditions have a wide range of optional contact conditions. According to a preferred embodiment of the present invention, the contact conditions include: a contact temperature of 30-180°C, preferably 50-110°C; the contact time can be reasonably determined according to actual needs, preferably 3-30h, preferably 6-20h.
[0059] In the present invention, in step S2, the second drying condition has a wide range of optional options. According to a preferred embodiment of the present invention, the second drying condition includes: a drying temperature of 70-200°C; the drying time can be reasonably determined according to actual needs, and the preferred drying time is 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.
[0060] According to another preferred embodiment of the present invention, the metal organic framework material is a copper-iron bimetallic MOFs material, comprising:
[0061] A bimetallic center formed by Fe and Cu containing two or more valence states; and
[0062] An organic ligand that hybridizes with a bimetallic center to form a three-dimensional network structure crystal through a coordination bond. In the copper-iron bimetallic MOFs material of the present invention, both metals are bonded to the organic ligand, and due to the interaction between the two metals, the metal valence state changes, forming more empty coordination sites, and the bimetallic MOFs material contains only L acid (Lewis acid) sites. The copper-iron bimetallic MOFs material of the present invention is used to synthesize pyrrole compounds (such as N-substituted pyrrole compounds), and also has the advantages of high reaction efficiency and high product yield.
[0063] In the present invention, the copper-iron bimetallic MOFs material contains only L acid, and the amount of L acid is 100-600 μmol·g -1 , preferably 150-400 μmol·g -1 .
[0064] In the prior art, the traditional catalytic method for preparing N-substituted pyrrole compounds uses B acid (protonic acid) as a catalyst, and this method is easily affected by the presence or absence of water in the reaction system. In the present invention, the method for preparing N-substituted pyrrole compounds uses the copper-iron bimetallic MOFs material of the present invention as a catalyst. Since the copper-iron bimetallic MOFs material only contains L acid sites, it can catalytically convert furan compounds and amine compounds to prepare N-substituted pyrrole compounds under mild reaction conditions, and prevent the generation of by-products such as 3-methyl-2-cyclopentenone. The method has high selectivity and high product yield; and since the catalyst material containing Lewis acid is used, it is not easy to corrode the equipment at high temperature; at the same time, since the reaction conditions are mild, it will not damage the structure of the copper-iron bimetallic MOFs material, thus providing a new idea for the application of MOFs in catalysis.
[0065] In the present invention, in the copper-iron bimetallic MOFs material, the types of the organic ligands can be selected from a wide range. According to a preferred embodiment of the present invention, the organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 4,4,4-tris(N,N-di(4-carboxylic acidphenyl)-amino)triphenylamine, 3,3,5,5-biphenyltetracarboxylic acid, imidazole, 2-methylimidazole, 2-nitroimidazole and 2-nitroimidazole derivatives; preferably at least one of trimesic acid and terephthalic acid.
[0066] The copper-iron bimetallic MOFs materials having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the copper-iron bimetallic MOFs material of the present invention, which comprises the following steps:
[0067] (I) dissolving the organic ligand and the Cu salt in a solvent, crystallizing, separating, and first drying to obtain a Cu-based MOFs material formed by Cu and the organic ligand;
[0068] (II), contacting the Cu-based MOFs material in step (I) with a water-alcohol mixture containing Fe element and Fe salt; separating and performing a second drying to obtain the copper-iron bimetallic MOFs material.
[0069] The preparation method of the copper-iron bimetallic MOFs material of the present invention utilizes the idea of self-reduction of multivalent transition metals and creatively adds elemental iron. Under the action of elemental iron, the modified solution has reducing properties, so that the effective reducing components can act to a greater extent. In addition to the reducing effect, the metallic iron can also provide more vacant sites to increase the acid content of the material, so that the multivalent copper-iron bimetallic MOFs material contains only L acid. In the copper-iron bimetallic MOFs material of the present invention, the metal ions and the carboxylic acid ligands form a binuclear metal paddle wheel structure at the node, and the coordinated water molecules are easily removed during the preparation process to form an open metal center as a catalytic center.
[0070] In the present invention, in step (I), the organic ligand and the Cu salt can be dissolved in a solvent to obtain a solution containing the organic ligand and a solution containing the Cu salt, respectively, and then the solution containing the organic ligand and the solution containing the Cu salt are mixed and reacted to obtain a Cu-based MOFs material.
[0071] In the present invention, in step (I), the range of crystallization conditions is relatively wide. According to a preferred embodiment of the present invention, the crystallization conditions include: a crystallization temperature of 30-150°C, preferably 60-110°C; the reaction time can be reasonably determined according to actual needs, preferably, the crystallization time is 3-24h, preferably 10-20h.
[0072] In the present invention, in step (I), the first drying condition has a wide range of optional conditions. According to a preferred embodiment of the present invention, the drying conditions include: a drying temperature of 70-200°C, and the drying time can be reasonably determined according to actual needs, and the drying time is 2-48h; preferably, the drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.
[0073] In the present invention, in step (II), the contact conditions have a wide range of optional contact conditions. According to a preferred embodiment of the present invention, the contact conditions include: a contact temperature of 30-150°C, preferably 50-90°C; the contact time can be reasonably determined according to actual needs, and the contact time is 3-24h, preferably 3-10h.
[0074] In the present invention, the Cu salt is at least one selected from soluble salts of metal Cu.
[0075] In the present invention, the Fe salt is at least one selected from soluble salts of metallic Fe.
[0076] In the present invention, in step (I), the range of solvents available is relatively wide. According to a preferred embodiment of the present invention, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, triethylamine, hydrofluoric acid, tetrahydrofuran, methanol, ethanol and deionized water.
[0077] In step (II), in the water-alcohol mixture, the alcohol is selected from C1-C5 monohydric alcohol or polyhydric alcohol, preferably at least one of methanol, ethanol, propanol and ethylene glycol.
[0078] In the present invention, in step (I), the ratio of the amount of solvent to the Cu salt can be selected in a wide range. According to a preferred embodiment of the present invention, the ratio of the amount of solvent to the salt containing the first metal is 5-100 mL solvent / 1.0 g Cu salt.
[0079] According to a preferred embodiment of the present invention, in step (II), the molar ratio of elemental Fe to soluble Fe salt is 1:0.1-10.
[0080] According to a preferred embodiment of the present invention, in step (II), the dosage ratio of the Fe salt is 5-200 mL solvent / 1.0 g.
[0081] In the present invention, the types of the amine compounds can be selected from a wide range. According to a preferred embodiment of the present invention, the amine compounds are selected from at least one of aniline, m-chloroaniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-hydroxyaniline, n-hexylamine, furfuralamine, naphthylamine, 2-thiophenemethylamine and benamine.
[0082] According to a preferred embodiment of the present invention, the furan compound is at least one selected from 2-methylfuran, 2,5-dimethylfuran and furan.
[0083] In the present invention, there is no particular limitation on the type of the liquid diluent, as long as it does not react with the substrate, conventional liquid diluents in the art can be used in the present invention. According to a preferred embodiment of the present invention, the liquid diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, n-hexane, dichloromethane, tetrahydrofuran, acetone and methyl isobutyl ketone.
[0084] In the present invention, the range of the optional amount ratio of 2,5-hexanedione and / or furan compounds to the catalyst is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of 2,5-hexanedione and / or furan compounds to the catalyst is 1-100:1, preferably 2-30:1.
[0085] In the present invention, the range of the optional dosage ratio of 2,5-hexanedione and / or furan compounds to amine compounds is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of 2,5-hexanedione and / or furan compounds to amine compounds is 0.2-100:1, preferably 0.5-50:1.
[0086] In the present invention, the range of the optional amount ratio of the liquid phase diluent to 2,5-hexanedione and / or furan compounds is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of the liquid phase diluent to 2,5-hexanedione and / or furan compounds is 0.1-200:1, preferably 5-50:1.
[0087] In the present invention, the contact conditions of 2,5-hexanedione and / or furan compounds with amine compounds can be selected in a wide range. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 100-220°C, preferably 120-200°C; and / or a time of 1-24h, preferably 4-20h.
[0088] In the present invention, the reaction product N-substituted pyrrole compound is analyzed qualitatively and quantitatively by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of the product soluble carbohydrate is analyzed by high performance liquid chromatography (HPLC). The gas chromatography-mass spectrometer is Agilent 7890A of Agilent Corporation of the United States, the chromatographic column is HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph is Agilent 7890B, the detector is hydrogen flame ionization detector (FID), and the chromatographic column is SE-54 capillary column (30m, 0.53mm). The high performance liquid chromatography adopts Agilent 1200 analysis, and the chromatographic column is SHODEX SC1011 sugar column (8×300mm).
[0089] The acid content and acid type of metal organic framework materials were determined by pyridine adsorption infrared method (Nicolet Model 710 spectrometer). The specific operation steps are as follows: a. Sample pretreatment. The sample (about 30 mg) was pressed into a thin disc with a diameter of 13 mm and loaded into the infrared sample tank. After that, the sample was pretreated for 1 hour under vacuum cell conditions and 150°C. After the sample tank was cooled to room temperature, the sample infrared data was scanned as the background. b. Pyridine adsorption. At room temperature and vacuum environment, pyridine vapor was introduced into the original position until the adsorption reached equilibrium, and the adsorption time was 1 hour. c. Pyridine desorption. After the adsorption was completed, vacuum was evacuated at 100°C until the internal pressure no longer changed. The desorption time was 40 minutes, and the infrared absorption spectrum was scanned and recorded respectively. The difference spectrum before and after pyridine adsorption is the obtained pyridine adsorption-infrared absorption spectrum. The acid content of the sample was semi-quantitatively calculated based on the spectrum:
[0090]
[0091]
[0092] Where r and w are the diameter (cm) and mass (g) of the catalyst disc, A is the absorbance integral value at the specified wave number peak based on the scanning pyridine adsorption-infrared absorption spectrum, IMEC is the integrated molar extinction coefficient, IMECL is 2.22, and IMECB is 1.67.
[0093] The XRD measurement method is: the phase of the sample is analyzed using a Rigaku Ultima IV X-ray powder diffractometer from Japan, with a CuKα ray source. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.
[0094] In the present invention, the contact angle measuring instrument is DSA100 of KRUSS Company of Germany. A tangent line of the gas-liquid interface is drawn from the intersection of the three phases of gas, liquid and solid, and the angle θ between the tangent line and the solid-liquid boundary line passing through the three-phase contact point is the contact angle of the liquid on the solid surface. When the gas is air, the solid is a metal organic framework material, and the liquid is water, the measured contact angle is the contact angle of the metal organic framework material with water, wherein the larger the contact angle, the better the relative hydrophobicity of the metal organic framework material.
[0095] In the present invention, the scanning electron microscope (SEM) photos of the samples were taken on a Hitachi S-4800II scanning electron microscope. The acceleration voltage of the instrument was 15 kV, and the samples were chrome-plated before analysis.
[0096] In the present invention, the test instrument and test method for the average pore size, specific surface area and pore volume of the sample are: physical adsorption measurement is performed by nitrogen at -196°C using a 3H-2000PM2 physical adsorption instrument to analyze the pore structure characteristics of each adsorption material sample. The initial degassing condition is: degassing operation at 150°C for 6 hours. After measuring the adsorption isotherm of nitrogen on the sample, the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) method, and the pore volume and pore size distribution are calculated using the BJH (Barrett-Joyner-Halenda) method.
[0097] The conversion rate of 2,5-hexanedione and / or furan compounds (%) = (molar amount of 2,5-hexanedione and / or furan compounds participating in the reaction) / (molar amount of 2,5-hexanedione and / or furan compounds as reaction substrates) × 100%.
[0098] The yield of the product N-substituted pyrrole compound (%) = (molar amount of N-substituted pyrrole generated by the reaction) / (molar amount of the reaction substrate 2,5-hexanedione and / or furan compound) × 100%.
[0099] The selectivity of the product N-substituted pyrrole (%) = (molar amount of N-substituted pyrrole produced by the reaction) / (molar amount of 2,5-hexanedione and / or furan compound reacted) × 100%.
[0100] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments, but the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0101] Example 1
[0102] S1. Weigh 3 g of trimesic acid and add it to a mixture of 70 mL of anhydrous ethanol and 40 mL of DMF, and stir thoroughly for 20 min. Weigh 6 g of copper nitrate trihydrate and dissolve it in 70 mL of H 2 O, and then the two solutions were mixed. After the mixture was fully stirred, it was placed in a reactor and crystallized at 85°C for 20 hours. After crystallization, it was cooled to room temperature, centrifuged to remove the mother liquor, and washed with ethanol several times. The drying was carried out in two stages. The temperature of the first stage was 75°C and the time was 4 hours. The drying temperature of the second stage was 150°C and the time was 10 hours. After that, it was vacuum dried at 100°C for 10 hours to obtain Cu-BTC.
[0103] S2, weigh 0.6g benzimidazole (BzIm) and add it to 80mL methanol, stir it thoroughly to obtain a methanol solution; weigh 1.2g Cu-BTC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir it thoroughly for 6h. The solution was placed in a reactor and crystallized at 80°C for 16h. After crystallization, it was cooled to room temperature, centrifuged to remove the mother liquor, and washed with methanol. Drying was carried out in two stages, the temperature of the first stage was 75°C and the time was 4h. After drying, it was soaked in dichloromethane for 48h, and it was replaced every 24h. The drying temperature of the second stage was 150°C and the time was 10h. After that, it was vacuum dried at 100°C for 10h to obtain hydrophobic Cu-BTC-BzIm.
[0104] The SEM images of samples Cu-BTC and Cu-BTC-BzIm are shown in Figure 1 As shown, the SEM image of Cu-BTC is Figure 1 As shown in (a), the crystal is a regular octahedron with a smooth surface and a crystal size of 12-18 μm. Figure 1 As shown in (b), the crystal form of Cu-BTC-BzIm has not changed significantly, but there are clustered flake-like protrusions on the surface, forming a wrinkled outer surface.
[0105] Pyridine desorption infrared spectroscopy of samples Cu-BTC and Cu-BTC-BzIm Figure 2 As shown by Figure 2 The total acid content of Cu-BTC-BzIm was calculated to be 178.6 μmol·g -1 The total acid content of Cu-BTC is 50.3 μmol·g -1 .
[0106] Cu-BTC has hydrophilicity because the ligands in the material are carboxylic acids. Figure 3 After modification with imidazole ligands containing benzene rings, Cu-BTC-BzIm material has a certain degree of hydrophobicity compared to Cu-BTC, and the contact angle test diagram is shown in Figure 4 As shown, the contact angle of Cu-BTC-BzIm with water is 78-81°.
[0107] The nitrogen adsorption and desorption curves of Cu-BTC and Cu-BTC-BzIm are as follows Figure 5 As shown; Among them, the specific surface area of Cu-BTC is 1572.8m 2 ·g -1 , external specific surface area 43.1m 2 ·g -1 , total pore volume 0.72cm 3 ·g -1 、0.62cm 3 ·g -1 ;
[0108] Cu-BTC-BzIm specific surface area 1316.1m 2 ·g -1 , external specific surface area 78.8m 2 ·g -1 , total pore volume 0.77cm 3 ·g -1 、0.38cm 3 ·g -1 Compared with Cu-BTC, the total specific surface area of Cu-BTC-BzIm material is reduced, but the external specific surface area is increased, the micropore volume is reduced, and therefore the mesopore / macroporous volume is increased.
[0109] Example 2
[0110] S1. Weigh 3 g of trimesic acid and add it to a mixture of 70 mL of anhydrous ethanol and 40 mL of DMF, and stir thoroughly for 20 min. Weigh 6 g of copper nitrate trihydrate and dissolve it in 70 mL of H 2O, and then the two solutions were mixed. After the mixture was fully stirred, it was placed in a reactor and crystallized at 85°C for 20 hours. After crystallization, it was cooled to room temperature, centrifuged to remove the mother liquor, and washed with ethanol several times. The drying was carried out in two stages. The temperature of the first stage was 75°C and the time was 4 hours. The drying temperature of the second stage was 150°C and the time was 10 hours. After that, it was vacuum dried at 100°C for 10 hours to obtain Cu-BTC.
[0111] S2, weigh 1.2g benzimidazole and add it to 80mL methanol, stir well to obtain a methanol solution. Weigh the Cu-BTC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir well for 6h. Then put the above solution into a reactor and crystallize it at 80°C for 16h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with methanol. Drying is carried out in two stages, the temperature of the first stage is 75°C and the time is 4h. After drying, soak it in dichloromethane for 48h, changing it every 24h. The drying temperature of the second stage is 150°C and the time is 10h. After that, vacuum dry it at 100°C for 10h to obtain hydrophobic Cu-BTC-BzIm-2.
[0112] The SEM image of Cu-BTC-BzIm-2 is as follows Figure 6 As shown, there are clusters of plate-like protrusions on the crystal surface, forming a wrinkled outer surface, and in contrast Figure 1 (b) The clustered lamellar protrusions are denser.
[0113] The total acid content of Cu-BTC-BzIm-2 is 159.3 μmol·g -1 , hydrophobic angle is 90°, specific surface area is 1200.7m 2 ·g -1 , external specific surface area 61.5m 2 ·g -1 , total pore volume 0.68cm 3 ·g -1 、0.35cm 3 ·g -1 .
[0114] Example 3
[0115] The method of Example 1 is followed, except that in step S2, 0.4 g of benzimidazole replaces 0.6 g of benzimidazole, and the remaining conditions are the same as those of Example 1, to obtain Cu-BTC-BzIm-3.
[0116] The SEM image of Cu-BTC-BzIm-3 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0117] The total acid content of Cu-BTC-BzIm-3 is 175.5 μmol·g -1 , the hydrophobic angle is about 72°, and the specific surface area is 1408.9m 2 ·g -1 , External specific surface area 55.2m 2 ·g -1 , total pore volume 0.7cm 3 ·g -1 、0.49cm 3 ·g -1 .
[0118] Example 4
[0119] The method of Example 1 is followed, except that in step S2, the amount of triethylamine used is 2.4 g; the other conditions are the same as those of Example 1, to obtain Cu-BTC-BzIm-4.
[0120] The SEM image of Cu-BTC-BzIm-4 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0121] The total acid content of Cu-BTC-BzIm-4 is 147.1 μmol·g -1 , the hydrophobic angle is about 65°, and the specific surface area is 1219.5m 2 ·g -1 , External specific surface area 50.7m 2 ·g -1 , total pore volume 0.61cm 3 ·g -1 、0.37cm 3 ·g -1 .
[0122] Example 5
[0123] The method of Example 1 is followed, except that in step S2, 80 mL of toluene is used instead of 80 mL of methanol, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-5.
[0124] The SEM image of Cu-BTC-BzIm-5 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0125] The total acid content of Cu-BTC-BzIm-5 is 166.2 μmol·g -1 , the hydrophobic angle is about 95°, and the specific surface area is 1299.3m 2 ·g -1 , external specific surface area 89.2m 2 ·g -1 , total pore volume 0.75cm 3 ·g-1 、0.32cm 3 ·g -1 .
[0126] Example 6
[0127] The method of Example 1 is followed, except that in step S2, 80 mL of ethanol is used instead of 80 mL of methanol, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-6.
[0128] The SEM image of Cu-BTC-BzIm-6 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0129] The total acid content of Cu-BTC-BzIm-6 is 177.9 μmol·g -1 , the hydrophobic angle is about 82°, and the specific surface area is 1357.8m 2 ·g -1 , external specific surface area 80.7m 2 ·g -1 , total pore volume 0.78cm 3 ·g -1 、0.41cm 3 ·g -1 .
[0130] Example 7
[0131] The method of Example 1 is followed, except that in step S2, 0.6 g of 2-methylbenzimidazole is used instead of benzimidazole, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-7.
[0132] The SEM image of Cu-BTC-BzIm-7 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0133] The total acid content of Cu-BTC-BzIm-7 is 170.4 μmol·g -1 , the hydrophobic angle is about 86°, and the specific surface area is 1309.2m 2 ·g -1 , external specific surface area 81.6m 2 ·g -1 , total pore volume 0.76cm 3 ·g -1 、0.39cm 3 ·g -1 .
[0134] Example 8
[0135] The method of Example 1 is followed, except that in step S2, 0.6 g of 5,6-dimethylbenzimidazole is used instead of benzimidazole, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-8.
[0136] The SEM image of Cu-BTC-BzIm-8 is similar to the morphology image of Cu-BTC-BzIm in Example 1.
[0137] The total acid content of Cu-BTC-BzIm-8 is 165.1 μmol·g -1 , the hydrophobic angle is about 91°, and the specific surface area is 1281.1m 2 ·g -1 , external specific surface area 82.3m 2 ·g -1 , total pore volume 0.69cm 3 ·g -1 、0.34cm 3 ·g -1 .
[0138] Example 9
[0139] The method of Example 1 is followed, except that in step S1, 2.4 g of terephthalic acid is used instead of 3 g of trimesic acid, and the other conditions are the same as those of Example 1, to obtain Cu-BDC-BzIm.
[0140] The crystals are multifaceted cubic.
[0141] The total acid content of Cu-BDC-BzIm is 125.8 μmol·g -1 , the hydrophobic angle is about 70°, and the specific surface area is 1003.5m 2 ·g -1 , External specific surface area 35.4m 2 ·g -1 , total pore volume 0.59cm 3 ·g -1 、0.3cm 3 ·g -1 .
[0142] Example 10
[0143] S1. Weigh 2.4 g of terephthalic acid and add it to a mixture of 70 mL of anhydrous ethanol and 40 mL of DMF, and stir thoroughly for 20 min. Weigh 7.38 g of zinc nitrate hexahydrate and dissolve it in 70 mL of H 2O, and then the two solutions were mixed. After the mixture was fully stirred, it was put into a reactor and crystallized at 85°C for 20 hours. After crystallization, it was cooled to room temperature, centrifuged to remove the mother liquor, and washed with ethanol several times. The drying was carried out in two stages. The temperature of the first stage was 75°C and the time was 4 hours. The drying temperature of the second stage was 150°C and the time was 10 hours. Then, it was vacuum dried at 100°C for 10 hours to obtain Zn-BDC.
[0144] S2, weigh 0.6g benzimidazole (BzIm) and add it to 80mL methanol, stir it thoroughly to obtain a methanol solution; weigh 1.2g Zn-BDC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir it thoroughly for 6h. Put the solution into a reactor and crystallize it at 80℃ for 16h. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with methanol. Drying is carried out in two stages, the temperature of the first stage is 75℃, and the time is 4h. After drying, soak it in dichloromethane for 48h, changing it every 24h. The drying temperature of the second stage is 150℃, and the time is 10h. Then, vacuum dry it at 100℃ for 10h to obtain hydrophobic Zn-BDC-BzIm.
[0145] The crystals are multifaceted cubic.
[0146] The total acid content of Zn-BDC-BzIm is 143.2 μmol·g -1 The hydrophobic angle is about 79° and the specific surface area is 1689.4m 2 ·g -1 , external specific surface area 85.3m 2 ·g -1 , total pore volume 0.89cm 3 ·g -1 、0.52cm 3 ·g -1 .
[0147] Embodiment 11
[0148] (I), weigh 3 g of trimesic acid (BTC) and add it to a mixture of 70 mL of anhydrous ethanol and 40 mL of DMF, and stir thoroughly for 20 min; weigh 6.0 g of copper nitrate trihydrate and dissolve it in 70 mL of H 2 O, and then mix the two solutions. After the mixture is fully stirred, put it into a reactor and crystallize it at 85°C for 20 hours. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with ethanol. Drying is carried out in two stages. The temperature of the first stage is 75°C and the time is 4 hours. The drying temperature of the second stage is 130°C and the time is 10 hours. After drying, Cu-BTC is obtained.
[0149] (II) Weigh 0.15g of ferrous sulfate and dissolve it in 20mL of water, then add 0.1g of iron powder, stir for 20min, add 100mL of ethanol, and stir for 20min to obtain an iron-containing solution. Weigh 2.0g of Cu-BTC prepared in step S1 and add it to the iron-containing solution, then place it in a water bath at 80°C and react for 6h. Then centrifuge to remove the mother liquor, wash it alternately with ethanol and water, and dry it to obtain Fe-Cu-BTC.
[0150] Pyridine desorption infrared images of Cu-BTC and Fe-Cu-BTC are shown in Figure 7 As shown by Figure 7 It can be seen that Fe-Cu-BTC contains only L acid (Lewis acid), with an acid content of 209.3 μmol·g -1 .
[0151] Depend on Figure 8 It can be seen that the characteristic peak positions of samples Fe-Cu-BTC and Cu-BTC are consistent, indicating that they have the same crystal form.
[0152] Example 12
[0153] (I), weigh 3g of trimesic acid (BTC) and add it to a mixture of 70mL of anhydrous ethanol and 40mL of DMF, and stir thoroughly for 20min; weigh 6g of copper nitrate trihydrate and dissolve it in 70mL of H 2 O, and then mix the two solutions. After the mixture is fully stirred, put it into a reactor and crystallize it at 85°C for 20 hours. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with ethanol. Drying is carried out in two stages. The temperature of the first stage is 75°C and the time is 4 hours. The drying temperature of the second stage is 130°C and the time is 10 hours. After drying, Cu-BTC is obtained.
[0154] (II) Weigh 0.25 g of silver nitrate and dissolve it in 20 mL of water. After stirring for 20 min, add 80 mL of ethanol and stir for 20 min to obtain a silver-containing solution. Weigh 2.0 g of the Cu-BTC prepared in step S1 and add it to the silver-containing solution, then place it in a water bath at 85°C and react for 6 h. Then centrifuge to remove the mother liquor, wash it alternately with ethanol and water, and dry it to obtain Ag-Cu-BTC.
[0155] Example 13
[0156] S1. Weigh 2.5g zirconium tetrachloride and 1.8g terephthalic acid and dissolve them in 80mL N,N-dimethylformamide to obtain solution A. Then transfer the above system to a crystallization kettle and crystallize at 120°C for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with ethanol several times. Drying is carried out in two stages. The temperature of the first stage is 75°C and the time is 4h. The drying temperature of the second stage is 160°C and the time is 12h. UiO-66 is obtained after vacuum drying.
[0157] S2. Weigh 1.0 g of the UiO-66 prepared above, place it in 100 mL of toluene, add chlorosilane to a molar concentration of 1.5 mM, and 2 The suspension was stirred at 130°C for 10 h under atmosphere. The suspension was then centrifuged, washed with toluene three times, and then vacuum dried at 160°C for 20 h to obtain hydrophobic UiO-66.
[0158] Embodiment 14
[0159] The method of Example 11 is followed, except that in step (II), 0.2 g of ferrous chloride is added instead of 0.15 g of ferrous sulfate, and the remaining conditions are the same as those of Example 1; Fe-Cu-BTC-2 is obtained.
[0160] The Fe-Cu-BTC-2 only contained L acid, and the acid content was 217.3 μmol·g -1 .
[0161] Examples 15-29
[0162] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g of the catalyst in Example 1-14, 2.0g of 2,5-hexanedione, 1.2g of aniline and 10g of methanol were added to a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 150°C for 6h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-hexanedione and the yield of the target product 2,5-dimethyl-1-phenylpyrrole, as shown in Table 1.
[0163] Table 1 Catalytic evaluation results of Examples 15-29
[0164]
[0165] Embodiment 30
[0166] The method of Example 15 is followed, except that the amount of catalyst used is 0.1 g, and the other conditions are the same as Example 15.
[0167] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 97.1%; and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.8%.
[0168] Embodiment 31
[0169] The method of Example 15 is followed, except that the amount of catalyst used is 0.5 g, and the other conditions are the same as Example 15.
[0170] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 98.9%; and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.5%.
[0171] Embodiment 32
[0172] The method of Example 15 was followed, except that the reaction was carried out at 180°C for 6 hours, and the other conditions were the same as those of Example 15.
[0173] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 99.7% and the yield of the target product 2,5-dimethyl-1-benzylpyrrole was 97.2%.
[0174] Embodiment 33
[0175] The method of Example 15 was followed, except that the reaction was carried out at 120°C for 6 hours, and the other conditions were the same as those of Example 15.
[0176] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 96.8% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.7%.
[0177] Embodiment 34
[0178] The method of Example 15 was followed, except that the reaction was carried out at 150°C for 12 hours, and the other conditions were the same as those of Example 15.
[0179] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 99.8% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.1%.
[0180] Embodiment 35
[0181] The method of Example 15 was followed, except that the amount of aniline used was 0.6 g, and the other conditions were the same as Example 15.
[0182] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 93.2% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 92.8%.
[0183] Embodiment 36
[0184] The method of Example 15 is followed, except that tetrahydrofuran is used instead of methanol, and the other conditions are the same as Example 15.
[0185] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 97.6%; and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.9%.
[0186] Embodiment 37
[0187] The method of Example 15 is followed, except that toluene is used instead of methanol, and the other conditions are the same as Example 15.
[0188] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 98.2% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 97.8%.
[0189] Embodiment 38
[0190] The method of Example 15 is followed, except that the amine compound is m-toluidine, and the other conditions are the same as Example 15.
[0191] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 98.1%; the yield of the target product 2,5-dimethyl-1-m-benzyl-1-H-pyrrole was 80.3%.
[0192] Embodiment 39
[0193] The method of Example 15 is followed, except that the amine compound is p-methoxyaniline, and the other conditions are the same as Example 15.
[0194] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 97.2%; the yield of the target product 1-(4-methoxyphenyl)-2,5-dimethyl-1H-pyrrole was 78.5%.
[0195] Embodiment 40
[0196] The method of Example 15 is followed, except that the amine compound is m-chloroaniline, and the other conditions are the same as Example 15.
[0197] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 99.2%; the yield of the target product 1-(3-chlorophenyl)-2,5-dimethyl-1H-pyrrole was 93.4%.
[0198] Embodiment 41
[0199] The method of Example 15 was followed, except that an equal amount of 2,5-dimethylfuran was used instead of 2,5-hexanedione, and the other conditions were the same as Example 15. The reaction solution was analyzed to obtain a 2,5-dimethylfuran conversion rate of 90.7% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 85.1%.
[0200] Embodiment 42
[0201] The method of Example 15 was followed, except that an equal amount of 2-methylfuran was used to replace 2,5-hexanedione, and the other conditions were the same as those of Example 15. The reaction solution was analyzed to obtain a 2-methylfuran conversion rate of 89.3% and a target product 2-dimethyl-1-phenylpyrrole yield of 82.3%.
[0202] Comparative Example 1
[0203] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g HY(37), 2.0g 2,5-hexanedione and 1.2g aniline were added into a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 150℃ for 6h. The reaction liquid was analyzed to obtain a 2,5-hexanedione conversion rate of 88.5% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 72.7%.
[0204] Comparative Example 2
[0205] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g H-Beta (100), 2.0g 2,5-hexanedione and 1.2g aniline were added to a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The heating jacket was heated to the preset temperature using a programmed temperature increase, and then stirred using a magnetic stirrer. The reaction was carried out at 150°C for 6h, and the reaction liquid was analyzed to obtain a 2,5-hexanedione conversion rate of 72.5%, and a target product 2,5-dimethyl-1-phenylpyrrole yield of 66.9%.
[0206] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an N-substituted pyrrole compound, characterized in that: The method includes: In the presence of a liquid diluent and a catalyst, 2,5-hexanedione and / or a furan compound is contacted with an amine compound; The catalyst contains a metal organic framework material, and the metal organic framework material includes: Metal center; and an organic ligand coordinated to the binding site of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities; The metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al; the organic ligand is selected from at least one of carboxylic acid organic ligands and / or polyazole organic ligands.
2. The preparation method according to claim 1, wherein The metal of the metal center is at least one of Zn, Cu, Ni, Fe, Co, Ag and Zr; and / or The carboxylic acid organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalenedicarboxylic acid, biphenyl dicarboxylic acid and 3,3,5,5-biphenyl tetracarboxylic acid; and / or The polyazole organic ligand is at least one selected from benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxybenzene)benzimidazole, 2-aminobenzimidazole and 2-(4'-thiazole)benzimidazole.
3. The preparation method according to claim 1 or 2, wherein The metal organic framework material is a dual ligand MOFs material, comprising: Metal center; and A carboxylic acid organic ligand and a polyazole organic ligand coordinated to at least two binding sites of the metal center to form an at least partially crystalline network structure having a plurality of internal pores.
4. The preparation method according to claim 3, wherein The metal organic framework material crystal has a wrinkled outer surface; preferably, clusters of flake-like protrusions are distributed on the surface of the metal organic framework material crystal to form a wrinkled outer surface; and / or The contact angle between the metal organic framework material and water is 40-120°, preferably 40-100°.
5. The preparation method according to claim 3, wherein: The total acid content of the metal organic framework material is 30-500 μmol·g -1 , preferably 40-400 μmol·g -1 ; and / or The total specific surface area of the metal organic framework material is 900-1800m 2 ·g -1 , external specific surface area is 40-200m 2 ·g -1 ; and / or The total pore volume of the metal organic framework material is 0.4-1.0 cm 3 ·g -1 , the micropore volume is 0.2-0.9cm 3 ·g -1 .
6. The preparation method according to claim 3, wherein: The preparation method of the dual-ligand MOFs material comprises the following steps: S1, dissolving a soluble metal salt and a carboxylic acid organic ligand in a solvent I, crystallizing, separating, and first drying to obtain a MOFs material formed by the metal and the organic ligand I; S2, contacting the MOFs material in step S1 with a solution containing polyazole organic ligands and alkaline substances; separating, washing, and performing a second drying to obtain the metal organic framework material.
7. The preparation method according to claim 6, wherein: In step S1, the molar ratio of the soluble metal salt to the carboxylic acid organic ligand is 1:0.2-5; and / or In step S1, the ratio of the solvent I to the soluble metal salt is 5-100 mL of solvent I / 1.0 g of soluble metal salt; and / or In step S2, the molar ratio of the MOFs material to the polyazole organic ligand is 1:(0.01-5); and / or In step S2, the molar ratio of MOFs material to alkaline substance is 1:(0.01-3); and / or In step S2, in the solution containing polyazole organic ligands and alkaline substances, the solvent is solvent II, and solvent II is selected from at least one of N, N-dimethylformamide, N, N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene and ethylbenzene, and the mass ratio of MOFs material to solvent II is preferably 1: (2-200); and / or In step S2, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, aqueous ammonia and aniline.
8. The preparation method according to claim 6, wherein: In step S1, the crystallization conditions include: a crystallization temperature of 30-200° C.; and / or a crystallization time of 3-44 h; and / or In step S1, the first drying condition includes: a drying temperature of 70-200°C; and / or a drying time of 2-48h; and / or In step S2, the contact conditions include: a contact temperature of 30-180°C; and / or a contact time of 3-30h; and / or In step S2, the second drying conditions include: a drying temperature of 70-200°C; and / or a drying time of 2-48 hours.
9. The preparation method according to claim 1 or 2, wherein: The metal organic framework material is a copper-iron bimetallic MOFs material, comprising: A bimetallic center formed by Fe and Cu containing two or more valence states; and An organic ligand that hybridizes with a bimetallic center through a coordination bond to form a stereo network structure crystal.
10. The preparation method according to claim 9, wherein: The copper-iron bimetallic MOFs material contains only L-acid, and the amount of L-acid is 100-600 μmol·g -1 , preferably 150-400 μmol·g -1 ; and / or The organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 4,4,4-tris(N,N-di(4-carboxylic acidphenyl)-amino)triphenylamine, 3,3,5,5-biphenyltetracarboxylic acid, imidazole, 2-methylimidazole, 2-nitroimidazole and 2-nitroimidazole derivatives; preferably at least one of trimesic acid and terephthalic acid.
11. The preparation method according to claim 9, wherein: The preparation method of the copper-iron bimetallic MOFs material comprises: (I) dissolving the organic ligand and the Cu salt in a solvent, crystallizing, separating, and first drying to obtain a Cu-based MOFs material formed by Cu and the organic ligand; (II), contacting the Cu-based MOFs material in step (I) with a water-alcohol mixture containing Fe element and Fe salt; separating and performing a second drying to obtain the copper-iron bimetallic MOFs material.
12. The preparation method according to claim 11, wherein In step (I), the crystallization conditions include: a crystallization temperature of 30-150° C.; and / or a crystallization time of 3-24 h; and / or In step (I), the first drying conditions include: a drying temperature of 70-200°C; and / or a drying time of 2-48h; and / or In step (II), the contact conditions include: a contact temperature of 30-150° C.; and / or a contact time of 3-24 h.
13. The preparation method according to claim 11, wherein In step (I), the ratio of solvent to Cu salt is 5-100 mL solvent / 1.0 g Cu salt; and / or In step (II), the molar ratio of elemental Fe to soluble Fe salt is 1:0.1-10; In step (II), the Fe salt is used in an amount ratio of 5-200 mL solvent / 1.0 g.
14. The preparation method according to claim 1 or 2, wherein: The amine compound is at least one selected from aniline, m-chloroaniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-hydroxyaniline, n-hexylamine, furfurylamine, naphthylamine, 2-thiophenemethylamine and benamine; and / or The furan compound is at least one selected from 2-methylfuran, 2,5-dimethylfuran and furan; and / or The liquid phase diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, n-hexane, dichloromethane, tetrahydrofuran, acetone and methyl isobutyl ketone.
15. The preparation method according to claim 1 or 2, wherein: The mass ratio of 2,5-hexanedione and / or furan compound to the catalyst is 1-100:1; and / or The mass ratio of 2,5-hexanedione and / or furan compound to amine compound is 0.2-100:1; and / or The mass ratio of the liquid diluent to 2,5-hexanedione and / or furan compounds is 0.1-200:1; and / or The contact conditions include: temperature of 100-220°C; And / or time is 1-24h.
Citation Information
Patent Citations
1,5-diaryl pyrrole derivative as well as preparation method and anti-tumor application thereof
CN103288701A
Preparation method and applications of porous metal organic skeleton material
CN104370820A
Metal organic framework material and preparation method thereof
CN107774329A